The echocardiographic and radiological profile of Clinically diagnosed congenital heart disease in children - Dr. Sandeep Bhaskar; Dr. Sneha P; Dr. Manjunath Babu R; Dr. Chithambaram (Pediatric Review: International Journal of Pediatric Research, 2021)
Introduction: Congenital heart disease (CHD) if diagnosed clinically early and confirmed by Chest X-ray and ECHO, can be appropriately managed. Objectives: To observe the clinical profile of CHD in clinically diagnosed CHD in children To correlate the clinical profile with radiological and echocardiographic findings in the study group. Methods: It’s a cross-sectional study. The duration was 18 months. All children in the age group of 1 month to 18years of age with history & clinical findings suggestive of CHDs were taken, assessed, subjected to Chest X-ray & 2 DECHO & were correlate. Results: Total no. of cases admitted during the study period was 5423, 624 had CHD among which 50 fulfilling the criteria were taken. Clinically CCHD was in 34%, ACHD in 66%. Clinical correlation with X-ray was 83% and with ECHO was 87 %. Conclusion: ACHD is more common, Chest x-ray findings correlated closely. ECHO correlation with the clinical diagnosis was very accurate especially in isolated lesions and some cases were identified which had been missed clinically. Hence Clinical Diagnosis with X-ray and ECHO helps in increased identification & earlier intervention of CHDs.